Role of charge compensation mechanism and defect dipoles on properties of Mn doped BCT ceramics - Redhu, Preeti; Sharma, Preeti; Hooda, Ashima; Singh, Anupinder; Sharma, Geeta; Punia, Rajesh (Ceramics International, 2021)
Single-phase Mn doped Barium Calcium Titanate (BCT) (Ba0.80Ca0.20Ti1-xMnxO3; x = 0.000, 0.005, 0.010, 0.015 and 0.020) lead free ceramics have been prepared by conventional solid-state reaction method. XRD studies and Rietveld refinement confirmed the existence of tetragonal phase (P4mm) for all prepared ceramic compositions. The average grain size increased up to x = 0.005 and thereafter it decreased with increase in Mn content in BCT compositions. Analysis of temperature-dependent dielectric study revealed phase transformation from tetragonal to cubic phase and defect dipole induced anomaly in paraelectric region of temperature-dependent dielectric constant ( epsilon'-T) curve. Degree of diffusiveness increased with Mn doping in BCT ceramics as confirmed by evaluating diffused phase transition (DPT) parameters (gamma and delta(c)) by Power Law fitting and width of diffused phase transition (D') obtained from derivative of epsilon'-T curve. Ferroelectric (P-E loops) study revealed that ceramic composition with x = 0.015 Mn content showed the highest remnant polarization (P-r) and maximum polarization (P-max) of 14.10 mu C/cm(2) and 24.20 mu C/cm(2) respectively. Enhancement in energy storage properties with applied electric fields have been observed at room temperature. Maximum energy storage density W-rec similar to 190.89 mJ/cm(3) with an efficiency of 48.63% has been obtained for x = 0.015. A large piezoelectric charge coefficient (d(33)) of 460 pC/N has been obtained for x = 0.020. The room temperature magnetic measurements shows feeble ferromagnetism for Mn doped samples. These studies suggest the application of these ceramics for multilayer ceramic capacitors, energy storage, and high power applications..
Keywords: Defect dipoles; Dielectric anomaly; Energy storage; Ferroelectric materials; ferromagnetic materials; Lead-free ceramics; Mn doped BCT; piezoelectric; Williamson-Hall (W-H)